(untitled) (Journal of actual problems of jurisprudence, 2019)
The modern period of development of the Republic of Kazakhstan is characterized by increased state control and supervision in the field of environmental protection and natural resources, the creation of an optimal system of government, management of environmental and natural resource use with maximum efficiency. Keywords: environmental security, subjects subsoil, protection of the environment, the principles of environmental protection, environmental management.